Processo de ensino de produção textual no ensino básico: um relato de experiência - Costa, Fabiano Brum da; Fuzer, Cristiane (Linguagens & Cidadania, 2016)
This paper presents an experience report on a writing workshop in a school context, with the use of text of opinion and guiding notes. The work is based on processual writing approach, in which the teacher provided feedbacks through guiding notes to students. The work was divided as follows: explanation of the proposal in the school, activities in the classroom (reading activities, text production, evaluation and rewriting), sending texts to local newspaper and verification of the results regarding of the process of writing.